Adoption of Climate Resilient Agricultural Technologies by Farmers in Nalgonda district of Telangana State (Indian Journal of Extension Education, 2022)
Over the past few decades, climate change has become inevitable. In the present scenario, the focus from yield intensification is switched over to the adaptation to climate change. Climate Resilient Agricultural (CRA) technologies are observed as the best adaptation options available which could enhance the resilience of agriculture. The present study investigates the extent to which CRA technologies are being adopted by the farmers in the National Innovations in Climate Resilient Agriculture (NICRA) project implemented villages of Nalgonda district in Telangana state. It further examined the association of profile characteristics of respondents with the extent of adoption of CRA technologies. A structured interview was used to obtain data from 120 respondents. Results revealed medium to high levels of adoption of CRA technologies by the farmers with renovation and/or use of farm ponds, introduction and raising of medium duration variety in red gram viz., LRG-52 and preventive vaccination in livestock among the highly adopted technologies. The profile characteristics viz., farm size, annual income, innovativeness, information seeking behaviour, achievement motivation, and Weather Based Agro Advisory Services had positive and significant association with the extent of adoption of CRA technologies by the farmers.